PEMANFAATAN BUDAYA DAN TEKNOLOGI LOKAL DALAM RANGKA PENGEMBANGAN SAINS - Hairida, Hairida (Jurnal Pendidikan Matematika dan IPA, 2010)
Science education can be developed based on the uniqueness and superiority of a region, including technology, culture and local (traditional). This study aims to identify and describe local cultural and technological environment of traditional agricultural communities the Malays and Dayaks in Pontianak regency still believed and used in maintaining life, and integrate the local culture and technology in the development of science-based learning the local culture. Qualitative approach to ethnographic studies (etnosains and etnoteknologi study) with emphasis on critical studies and interpretive conducted in order to explore local culture and technological environment of traditional agricultural communities the Malays and Dayaks in observation techniques and in-depth interviews. The results showed that in culture and traditional local technology community agricultural environment Malays and Dayak tribes identified science concepts that can be developed in science learning in schools. Keywords: local culture, local technology, science